Effects of Experiential Avoidance and Family Emotional Support on the Parental Psychological Flexibility of Mothers of Preschoolers - Zhang, Bingkun; Garandeau, Claire; Lahtinen, Oskari (wiley, 2026)
Objective: This study examined the main and interactive effects of experiential avoidance and emotional support from families of origin and in-laws on the parental psychological flexibility (PPF) of mothers of preschoolers. Background: PPF is a key component of parenting quality and is closely linked to child development. While experiential avoidance has been identified as a psychological factor, few studies have examined the role of family emotional support, and none have distinguished between support from family of origin and in-laws. Method: This study used self-reported data from 335 Chinese mothers of preschoolers and hierarchical regression analyses. Results: Higher experiential avoidance was associated with lower PPF. Emotional support from family of origin was positively associated with PPF, whereas support from in-laws was negatively associated with it. A significant interaction showed that among mothers with high experiential avoidance, greater support from in-laws was related to lower PPF. Conclusion: This study provides a comprehensive examination of factors – both psychological and environmental – related to PPF. It highlights the complexity of family support systems by showing that support from family of origin may be beneficial, but support from in-laws may not. Implications: Interventions to enhance PPF should address both individual psychological factors and the source of family support.
Keywords: Parental Psychological Flexibility; Experiential Avoidance; Emotional Support; Family Systems Theory; Mothers of Preschool Children